PsycEXTRA Dataset 2010
DOI: 10.1037/e572992012-468
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of radio electric auricular treatment for stress-related disorders: A double-blinded, placebo-controlled controlled pilot study

Abstract: Background: The aim of this double-blind randomized study is to test the efficacy of a radio electric stimulator device using an auricular reflex therapy protocol for stress-related symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…To expose mouse R1 ES cells to Wi-Fi RF energy, we used a REAC apparatus that was originally designed to use the effects produced by the interaction between the electromagnetic field of the human body (27) and that produced by the instrument working with typical range frequencies of 2.4, 5.7, or 10.5 GHz, selectable by operator. REAC stimulation has previously been shown to be efficacious in ameliorating stress-related depression and anxiety (3,14,21–23).…”
Section: Resultsmentioning
confidence: 99%
“…To expose mouse R1 ES cells to Wi-Fi RF energy, we used a REAC apparatus that was originally designed to use the effects produced by the interaction between the electromagnetic field of the human body (27) and that produced by the instrument working with typical range frequencies of 2.4, 5.7, or 10.5 GHz, selectable by operator. REAC stimulation has previously been shown to be efficacious in ameliorating stress-related depression and anxiety (3,14,21–23).…”
Section: Resultsmentioning
confidence: 99%
“…In Rinaldi et al [22] it was found that REAC can be an alternative therapy for stress-related disorders. Based on the randomized control study, 150 people in the group treated with REAC found a significant reduction in Psychological Stress Measure (PSM) scores, compared to 50 people in the control group who received a placebo.…”
Section: Reac Efficacy On Stressmentioning
confidence: 99%
“…In addition, REAC also optimizes the response to stressors so that it can cause a decrease in dysfunctional adaptive behavior [15]. In addition, REAC is also known to be an effective instrument for improving responses to allostatic conditions and environmental stressors [22].…”
Section: Reac Efficacy On Stressmentioning
confidence: 99%
“…We can use auricular electroacupuncture, which is less invasive, of less cost, and convenient to treat diseases by setting up suitable parameters. Recently, kinds of acupuncture treatment instruments such as radio electric stimulator device [ 43 ] and P-Stim auricular electroacupuncture stimulation device [ 44 ] have been developed for the treatment of stress-related disorders and pain relief. Auricular vagal nerve stimulator is expected to be explored.…”
Section: Potential Application Of Auricular Acupuncture For Other mentioning
confidence: 99%